Responsible innovation in venture creation and firm development: the case of digital innovation in healthcare and welfare services - Raj Kumar Thapa; Tatiana Iakovleva (Journal of Responsible Innovation, 2023)
ABSTRACTThe increasing adaptation of digitalisation has engendered numerous venture ideas and entrepreneurial opportunities. Many of these ideas bear the potential to address grand societal challenges. However, perceived opportunities can be elusive, especially in the context of complex problems. Opportunity confidence (OC) can be essential to venture creation and firm development. OC depends on evaluating socioeconomic, socio-ethical, and socioecological factors, which are not straightforward. Responsible innovation (RI) can be a viable approach to building OC. However, whether or how firms and entrepreneurs pursue RI to build OC needs to be clarified. Accordingly, we explore these issues through a case study of nine for-profit firms in digital healthcare and welfare services. The findings reveal that although the firms do not integrate RI principles in innovation and entrepreneurial activities per se, they practice them to varying degrees. This helps them to build OC. The study contributes to theory, practice, and policy.